Philosophical Reflections on Facilitating Paradigm Shifts - Herndon, J. Marvin (Advances in Social Sciences Research Journal, 2021)
A paradigm shift by definition is a major change in scientific understanding that upends and replaces a prior paradigm. Over the past 47 years, I have made a number of paradigm shifts in the geosciences, planetary sciences, and astrophysical sciences. These include the composition of the inner core and deep interior of Earth, recognizing that Earth’s early formation as a Jupiter-like gas giant makes it possible to derive virtually all the geological and geodynamic behavior of our planet, including the origin of mountains characterized by folding, the primary initiation of fjords and submarine canyons, the origin and typography of ocean floors and continents (described in Whole-Earth Decompression Dynamics), which upends and replaces plate tectonics theory, Earth’s previously unanticipated, powerful, and variable energy sources, namely, a terra-centric nuclear fission georeactor and the stored energy of protoplanetary compression, the nuclear georeactor origin of Earth’s magnetic field and the reasons for its variability. I also revealed a new concept that explains the thermonuclear ignition of stars and, concomitantly, the dark matter surrounding galaxies, the origin of heavy elements, and the reason why the vast multitude of galaxies in the universe display just a few prominent patterns of luminous stars. Recently, I discovered that particulate pollution, not carbon dioxide, is the primary cause of anthropogenic global warming. These are paradigm shifts which, unless successfully refuted, provide new, more-correct logical pathways for future discoveries. Here I reflect on some aspects of my personal science philosophy that has facilitated these fundamental paradigm shifts.